2008
DOI: 10.1530/rep-08-0157
|View full text |Cite
|
Sign up to set email alerts
|

Excess estrogen sulfoconjugation as the possible cause for a poor sign of parturition in pregnant cows carrying somatic cell clone fetuses

Abstract: We conducted this study to elucidate a factor causing a poor sign of parturition and prolonged gestation, which is frequently observed in cows carrying somatic clone fetuses. Pre-partum rises in concentrations of plasma estrone and estradiol-17b in the recipient cows pregnant with clones were subtle. By contrast, the plasma concentration of estrone sulfate in clone pregnancies increased gradually from pre-initiation of parturition induction whereas control cows that received in vivo-derived embryos showed a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 37 publications
2
20
0
Order By: Relevance
“…The lack of a significant difference among CBW group for the gestation length was probably due to low number of observations in the trial; however, the numerical scale and the result from the contrast BWT-A, BWT-B versus BWT-C is consistent with the discussion of Hirayama et al [18] about the effect of sulfoconjugation and the signs of parturition.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The lack of a significant difference among CBW group for the gestation length was probably due to low number of observations in the trial; however, the numerical scale and the result from the contrast BWT-A, BWT-B versus BWT-C is consistent with the discussion of Hirayama et al [18] about the effect of sulfoconjugation and the signs of parturition.…”
Section: Discussionsupporting
confidence: 79%
“…Second, however, we must consider that both groups of pregnancies were derived from IVPE system, and this could be another variable that has a greater effect on CBW than the origin of the bull [19]. We are not aware of a possible effect of IVPE system per se on the expression of estrogen sulfotransferase (SULT1E1), which could be affected by cloning as reported in the article by Hirayama et al [18]; however, their comparison was done with in vivo-fertilized embryos rather than in vitro. Therefore, it is not possible to conclude, if alteration of parturition is due to the clonal origin or the large offspring syndrome, that it is also described, albeit at much lower frequency, for pregnancies from IVPEs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These findings imply that disruption of cortisol secretion in clone fetuses is a principal cause of the problems in the peripartum period. Chavatte-Palmer et al [3] reported that the responsiveness of the adrenocortical tissue to adrenocorticotrophin in clone calves is normal, and we have also shown that clone calves had the ability to secrete cortisol at parturition [9]. However, the secretion of cortisol in prepartum clone fetuses is not fully understood.…”
mentioning
confidence: 59%
“…Furthermore, cortisol downregulates fetal growth and stimulates the maturation of those organs essential for extrauterine survival, such as the lungs and thyroid [8]. Previously, we reported an insufficient increase of the prepartum estrogen concentration in pregnant cows carrying a clone fetus [9]. LOS and respiratory distress syndrome are also frequently observed in neonatal clone calves [2].…”
mentioning
confidence: 95%